Optimalisasi Pelaksanaan Shipboard Oil Pollution Emergency Plan Dalam Menanggulangi Pencemaran Minyak Di Kapal Mt. Sp 5 Bsi - Naufal, Nabil; Huda, Samsul; Riyadi, Slamet (Jurnal Cakrawala Bahari, 2023)
SOPEP (Shipboard Oil Pollution Emergency Plan) is an emergency plan for oil pollution at sea and in accordance with MARPOL 73/78 these requirements are regulated in Annex I, with guidelines set by MEPC (Marine Environmental Protection Committee). The aim of the research is to determine the implementation of SOPEP in dealing with oil pollution for the safety of MT ship crews. SP 5 BSI.In this research the author used a qualitative research method, a qualitative method, namely a research method that is descriptive and tends to use analysis.The research results show that the implementation of SOPEP as a tool for dealing with oil pollution is still not appropriate. This can be proven that the ship’s crew does not understand how to use SOPEP according to applicable regulations and doesn’t understanding of how to use oil Spill prevention equipment.